CFRP strengthened steel beams: Improvement in failure modes and performance analysis. (November 2017) - Selvaraj, Sivaganesh; Madhavan, Mahendrakumar
Abstract: The externally bonded CFRP strengthened steel C channel beams were tested in this study to understand the improvement in failure modes. Two different CFRP strengthening methods were proposed: 1) surface strengthening (wrapping around perimeter); 2) closed strengthening in which the open cross section of the steel channel section is infilled with cardboard and converted into a closed rectangular cross section followed by CFRP wrapping to improve the buckling mode. In addition, the effectiveness of CFRP strengthening under environmental exposure is also studied by conducting the durability test with artificial rain. The results indicate that the CFRP strengthening technique employed in the present research work can significantly improve the flexural moment capacity compared to the unstrengthened specimen by converting the lateral torsional buckling (LTB) mode of failure to failure due to yielding. The durability test indicates that the infill cardboard material is not affected due to moisture exposure. Highlights: An experimental study on CFRP strengthened steel channel beams is presented. The effects of various strengthening parameters are examined. Remedy to overcome the CFRP local buckling and delamination is addressed. The effective strengthening technique for steel open channel beams is proposed.